(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes modern and innovative approaches to teaching watercolor techniques to children (preschool and primary school age) within the context of supplementary and general art education. It examines the challenges of traditional methods, the role of digital and integrative technologies, active and playful methods, and methods focused on developing cognitive and performance skills.